Analysis of Factors Associated with the Use of an Electronic Medical Record Information System Based on the Technology Acceptance Model (TAM) - Tekayana, I Wayan Pasek; Susanti, Ni Luh Putu Dina; Wahyunigsih, Luh Gde Nita Sri; Sagitarini, Ni Putu Noviana (GLOBAL HEALTH SCIENCE GROUP, 2024)
A crucial sector in the Health system which is included in the 6 pillars of Health transformation is Health technology transformation. Health technology transformation has a role in utilizing technology and biotechnology in the health sector. One use of technology in health services globally is the use of Electronic Medical Records (RME). Technology acceptance model (TAM) is used to predict the use and acceptance of an information system and technology by individual users, which will influence the success or failure of implementing a new information system. The purpose of writing this literature review is to analyze factors related to the use of electronic medical recordsTechnology acceptance model(TAM).Method:The method used in this writing is a literature review. The research articles used were obtained through a literature search using an online database, namely Google Scholar, which was published from 2019 to 2024. The keywords used in the database search were